Adverse events in the treatment of spinal muscular atrophy in children and adolescents with nusinersen: A systematic review and meta-analysis - Zhong, Zhi-Juan; Zheng, Pi-Mei; Dou, Hui-Hong; Wang, Ji-Gan (Frontiers in Pediatrics, 2023)
Objectives: To systematically analyze adverse events (AEs) in treatment of spinal muscular atrophy (SMA) with Nusinersen in children. Methods：The study is registered on PROSPERO (CRD42022345589). Databases were searched and literature relating to Nusinersen in the treatment of spinal muscular atrophy in children from the start of database establishment to December 1, 2022, was retrospectively analyzed. R.3.6.3 statistical software was used, and random effects meta-analysis was performed to calculate weighted mean prevalence and 95% confidence intervals (CI). Results: In total, 15 eligible studies were included, with a total of 967 children. Rate of definite Nusinersen-related AEs was 0.57% (95% CI: 0% -3.97%), and probable Nusinersen-related AEs 7.76% (95% CI: 1.85% -17.22%). Overall rate of AEs was 83.51% (95% CI: 73.55% -93.46%), and serious AEs 33.04% (95% CI: 18.15% -49.91%). For main specific AEs, fever was most common, 40.07% (95% CI: 25.14% -56.02%), followed by upper respiratory tract infection 39.94% (95% CI: 29.43% -50.94%), and pneumonia 26.62% (95% CI: 17.99% -36.25%). The difference in overall AE rates between the two groups was significant (OR = 0.27,95% CI: 0.08-0.95, P = 0.042). Moreover, incidence of serious adverse events, and fatal adverse events were both significantly lower than in the placebo group (OR=0.47, 95%CI: 0.32-0.69, P<0.01), and (OR=0.37, 95%CI: 0.23-0.59, P<0.01), respectively. Conclusion: Nusinersen is effective for treatment of spinal muscular atrophy in children. Direct adverse events are rare, and Nusinersen effectively reduces common, serious, and fatal adverse events in children with spinal muscular atrophy.